Geochemical characteristics of geothermal and hot spring gases in Beijing and Zhangjiakou Bohai fault zone - Yang, Mingbo; Liu, Guiping; Liu, Zhe; Ma, Jingchen; Li, Liwu; Wang, Zhiguo; Hua, Peixue; Xing, Lantian; Sun, Xiaoru; Han, Kongyan; Cui, Bowen; Wu, Xiaodong (Frontiers in Earth Science, 2022)
The Beijing and Zhangjiakou-Bohai Fault Zone is a group of NW-W orderly active fault zones with high seismic activity and abundant geothermal resources since the Cenozoic. Many violent earthquakes occurred here, where it was an important area for earthquake monitoring and research. In order to explore the temporal and spatial variation characteristics of gas geochemistry in the Zhangjiakou-Bohai Fault Zone of the capital circle, this study cited the previous two-stage survey data of 23 geothermal hot springs in the west and east of the Zhangjiakou-Bohai Fault Zone of the capital circle in 2013 and 2018. In order to fill the gap in hot spring gas geochemistry in Beijing (the middle of the Zhangjiakou-Bohai Fault Zone), 21 emergent gas samples from hot springs were collected after many field surveys from October 2020 to November 2021. The test results of 44 gas samples with chemical compositions and isotope changes of helium, neon, and carbon showed that: (1) The helium isotope ratio (3He/4He (Rc/Ra)) of hot spring gases in the Zhangjiakou-Bohai Fault Zone ranged between 0.03 and 2.86Ra (Ra = air, 3He/4He = 1.39 × 10−6), and the calculated maximum proportion of mantle-derived helium was up to 35.4%. It was revealed that although the geological fluid in the fault zone mainly came from crustal source, the mantle-derived helium was still considerable. The hot spring gases in Beijing (the middle of the Zhangjiakou-Bohai Fault Zone) were mainly composed of nitrogen, whose concentration was more than 69%, featuring a low CO2 concentration of 0–6.1% and a δ13CCO2 value ranging from −19‰ to −9.6‰ (vs.PDB) and showing the mixing characteristics of organic sediments and mantle sources. (2) The upwelling release of mantle-derived materials in Zhangjiakou-Bohai Fault Zone shared a good corresponding relationship with regional seismicity, which could promote the inoculation and occurrence of regional earthquakes. In the peak area, the transition zone from the western mountainous area of the Zhangjiakou-Bohai Fault Zone to the plain showed that more mantle-derived materials upwelled, and more deep fluid upwelled. The comparative analysis of regional seismicity showed that deep fluid played an important role in controlling regional seismicity in the area with relatively strong upwelling of deep fluid in the Zhangjiakou-Bohai Fault Zone.